2013
DOI: 10.1104/pp.113.229393
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Induced Conditional Rescue of the Reduced Epidermal Fluorescence8 Mutant of Arabidopsis Reveals Rapid Restoration of Growth and Selective Turnover of Secondary Metabolite Pools

Abstract: The phenylpropanoid pathway is responsible for the biosynthesis of diverse and important secondary metabolites including lignin and flavonoids. The reduced epidermal fluorescence8 (ref8) mutant of Arabidopsis (Arabidopsis thaliana), which is defective in a lignin biosynthetic enzyme p-coumaroyl shikimate 39-hydroxylase (C39H), exhibits severe dwarfism and sterility. To better understand the impact of perturbation of phenylpropanoid metabolism on plant growth, we generated a chemically inducible C39H expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…Mutating genes within the lignin/phenylpropanoid network frequently lead to plants with diminished growth, which had been presumed to be a side effect of the altered lignin [98]. This hypothesis has begun to be overturned by the application of a suppressor screen wherein Arabidopsis ref8 mutants deficient in p-coumaroylshikimate 3 -hydroxylase (C3 H) was screened for second site mutations that rescued growth of this genotype.…”
Section: Metabolic Feedback Loop Involving Phenylpropanoids and The Mmentioning
confidence: 98%
See 1 more Smart Citation
“…Mutating genes within the lignin/phenylpropanoid network frequently lead to plants with diminished growth, which had been presumed to be a side effect of the altered lignin [98]. This hypothesis has begun to be overturned by the application of a suppressor screen wherein Arabidopsis ref8 mutants deficient in p-coumaroylshikimate 3 -hydroxylase (C3 H) was screened for second site mutations that rescued growth of this genotype.…”
Section: Metabolic Feedback Loop Involving Phenylpropanoids and The Mmentioning
confidence: 98%
“…Key evidence that metabolites and/or their direct consequences have the capacity to generate a feedback loop to regulate transcription and properly coordinate a regulatory network has come from the study of metabolic mutants affecting plant phenylpropanoid metabolism [70,98,99]. Mutating genes within the lignin/phenylpropanoid network frequently lead to plants with diminished growth, which had been presumed to be a side effect of the altered lignin [98].…”
Section: Metabolic Feedback Loop Involving Phenylpropanoids and The Mmentioning
confidence: 99%
“…Alternatively, BGLU15 mediated turnover of flavonol bisglycosides may have important consequences for plant growth and development. Hyper-accumulation of kaempferol bisglycosides, including K3G7R, in an Arabidopsis mutant deficient in the lignin biosynthesis enzyme p-coumaroyl shikimate 3 0 -hydroxylase is associated with dwarfism; transformation of the mutant with a chemically inducible form of this enzyme confers a rapid loss of flavonol bisglycosides, followed by renewed stem inflorescence development due to increased lignin deposition (Kim et al, 2014). (1) and/or Q3G7R (2) levels.…”
Section: Recombinant Bglu15 Displays Preference For Flavonol 3-o-bglumentioning
confidence: 99%
“…Notably, peaks identified as flavonol 3-O-b-rutinoside-7-O-arhamnosides are consistent with nomenclature devised by Olsen et al (2009), although the possibility remains for their identification as flavonol 3-O-b-neohesperidoside-7-O-a-rhamnosides (Saito et al, 2013;Yonekura-Sakakibara et al, 2008) since UHPLC-DAD-MS n technology yields identical ion fragments for either conjugate. Kim et al (2014) established that minor degradation of kaempferol bisglycosides occurs during the development of the rosette habit stage in Arabidopsis when cultivated under non-stressed conditions. No such phenomena were observed here, as flavonol bisglycoside levels remained low and stable under constant NSHT (control; Fig.…”
Section: Introductionmentioning
confidence: 98%
“…For example in transgenic maize have been reported that overexpression of GH11 (xynB) gene lead to enhances biomass enzymatic digestibility [93], while in poplar have showed that GH10 (xyn10A) gene by RANi silencing increasing biomass yield [94].…”
Section: Hemicellulose Biosynthesis and Degradationmentioning
confidence: 99%